About regularities of technological parameters influence on accident–free mining of flat coal seams by plow systems - Demydov, M.S.; Shapovalov, Ya.A.; Astafiev, D.O.; Demchenko, Yu.I. (Розробка родовищ, 2014)
Analysis of research and publication on concerned topic is given. Analysis of stratigraphic columns of investigated seam is executed. Distance influence from wall face on loading character of mechanized support sections is determined. Regularities of loading changing on support sections at different advance rate of stoping face are substantiated. Наведено аналіз досліджень і публікацій за даною тематикою. Виконано аналіз стратиграфічних колонок досліджуваного пласта. Визначено вплив відстані від груді вибою на характер навантаження секцій механізованого кріплення. Обґрунтовано закономірності зміни навантаження на секції кріплення при різних швидкостях посування вибою. Приведен анализ исследований и публикаций по данной тематике. Выполнен анализ стратиграфических колонок исследуемого пласта. Определено влияние расстояния от груди забоя на характер нагружения секций механизированной крепи. Обоснованы закономерности изменения нагрузки на секции крепи при различных скоростях подвигания забоя.